Effect of particle size and physical form on digestibility of sun-cured alfalfa for pregnant sows - Nuzback, L.J.; Pollmann, D.S.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixteen pregnant crossbred sows (second parity) were employed in a digestion trial to evaluate the effect of particle size and physical form of sun-cured alfalfa. The treatment consisted of 1/4 inch meal, 1/4 inch pelleted, 1/2 inch meal, and ½ inch meal pelleted. Utilization of dry matter (DM), digestible energy (DE) and fiber components increased (P<.05) with the 1/4 inch particle size compared to 1/2 inch. Nitrogen utilization was not affected by the two particle sizes. Cellulose digestibility increased (P<.05) when pelleted but other digestion coefficients were not affected. During the third trimester, digestibility of DM, energy and fiber components increased (P<.05) compared to the first trimester. Apparent nitrogen digestibility increased (P<.05) in the third trimester but nitrogen balance and nitrogen retention decreased. The results of this study indicate that alfalfa is equally digested as meal or pellets and increased utilization by gestating sows can be expected with decreased particle size.
Keywords: Swine; Particle size; Digestibility; Sun-cured alfalfa